Comparative economics of system of rice intensification (SRI) in Tripura state of North-East India - Debbarma, Beauty; Ram Singh (Umiam, CPGS, CAU, 2011)
Rice is the important crop of India and it occupies 23.3 per cent of gross cropped area of the country. Area under rice in Tripura is 237 thousand ha with production and productivity of 624.66 thousand metric ton and 2.51 Uha respectively. Among the rice producing technology, SRI is modern method of rice production. Area under SRI in Tripura State is increasing year by year. The state is facing a deficit of 3. 1 lakhs ton of paddy. Keeping in view, three objectives viz. to work out the comparative economics of rice under SRI and Non-SRI methods, to analyze inputoutput relationship of both the technologies and to examine the constraints in rice cultivation and suggest measures to overcome the same were under taken in the study. The study was conducted in two districts viz. Dhalai and West of Tripura State of NEH region. One block from each district viz. Salema and Bishalgarh from Dhalai and West on the basis of area were selected, respectively. Two villages from each block were selected on the basis of highest area under. From each village, 30 rice growers, comprising of 15 SRI and 15 Non-SRI farmers were selected to make the sample size of 120 respondent in both the district. Both primary and secondary data were used in the study. The cost concept, linear regression and Garrett's ranking technique was used to analyse the primary household data. The study revealed that the average yield of SRI farmers of Dhalai and West was comparatively higher than Non-SRI farms in both the districts. The net income of SRI farmers was found 25 per cent higher than Non-SRI farmers of Dhalai district. Whereas, the net income of SRI farmers was found 48 per cent higher than Non-SRI farmers of west district. Cost A? for SRI was ` 16888.94 and `16884.42 in Dhalai and West districts, respectively. Whereas, Cost AI for Non-SRI farm was `19591.80 and `18363.82 in Dhalai and West district, respectively. Cost B? found more on small category under SRI in both districts. Whereas, it was found more on marginal farm under Non-SRI compared to small category farm in Dhalai district and viceversa in West district. It may be due to high rental value of land. Cost C? for SRI and Non-SRI farms accounted ` 35564.68 and `49766.80 in Dhalai, whereas, Cost C?- for SRI and Non-SRI farms accounted `82994.78 and `98516.46 in West district. It showed that SRI farmers of small category imputed more family labor than marginal category under both the districts. Under Non-SRI method, imputed family labor was more on marginal farm compared to small farm in Dhalai district which was viceversa in West district. The linear regression equation indicated that the variable fertilizer and plant protection measures were significant in SRI farm. Whereas, the fertilizer and seed were found negatively significant in Non-SRI farm. Among the various problems faced by the farmers during rice production non availability and high price of labor, less yield due to drought, non availability and high prices of fertilizer, lack of irrigation facilities, non availability of HYV-seeds, non availability of extension services, less yield due to flood and non availability of farm implements were found severe. Hence, SRI being a resource conserving technology, its benefits must be realized through extension workers. Agri-inputs should be availed through public-private-pertnership (PPP) to encourage the SRI method in the state.
Keywords: System of Rice Intensification (SRI) -- Cultivation methods; Rice-production; Tripura